2022
DOI: 10.4274/tjo.galenos.2021.98046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Culture-Positive and -Negative Microbial Keratitis

Abstract: Objectives: To evaluate and compare the risk factors, presenting features, and outcomes of patients with culture-positive and culturenegative microbial keratitis (MK) who presented to a tertiary referral center. Materials and Methods: We conducted a retrospective review of the medical records of 314 patients who were diagnosed with MK in our clinic between 2012 and 2019. Results: Among 314 patients, 142 had positive cultures (45.2%). The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
3
7
0
1
Order By: Relevance
“…Furthermore, other factors such as age and sex did not differ significantly between the groups. Similar results were reported by Bhandage et al (12) and Yarımada et al (20) who found that the initial and final visual acuity did not differ between the CP and CN groups.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, other factors such as age and sex did not differ significantly between the groups. Similar results were reported by Bhandage et al (12) and Yarımada et al (20) who found that the initial and final visual acuity did not differ between the CP and CN groups.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggest a trend towards worse visual outcomes in culture-positive IK, but the difference did not reach statistical significance in their study. Yarimada et al [ 21 ], in their study of 314 IK patients, found no statistically significant difference in BCVA between culture-positive and culture-negative patients at the end of the follow-up (p = 0.716). The mean BCVA for culture-positive patients was 1.21 ± 1.30 LogMAR, while it was 1.27 ± 1.29 LogMAR for culture-negative patients.…”
Section: Discussionmentioning
confidence: 97%
“…This finding was consistent with our study, which found that BCVA at presentation was statistically significantly worse in culture-positive patients than in culture-negative patients (p-value 0.001). However, some studies have found differences in BCVA at presentation between patients with culture-positive and culture-negative IK, but no statistically significant difference [ 21 , 22 ]. In the study by Bhadange et al [ 22 ], which included 60 patients with IK, the mean BCVA at the last follow-up was 1.83 LogMAR for culture-positive IK and 2.34 LogMAR at presentation for culture-negative IK.…”
Section: Discussionmentioning
confidence: 99%
“…21 Wearing contact lenses is a risk factor for microbial keratitis. 22 There were no fungal organisms isolated in the 2018 study compared with Koetsie et al, where 3.0% of the total organisms were fungi; this seems to be a substantial change. 2 Proxenos et al, who conducted a similar study in Durban, South Africa, had 2.5% fungal growths (n = 5/199) in corneal scrapes (although their study period was over four years -2016 to 2019).…”
Section: Discussionmentioning
confidence: 70%